Religion, sex and politics: Scripting connections in Romans 1:18–32 and Wisdom 14:12–14 - Punt, J. (HTS teologiese studies, 2017)
Ancient people envisaged a strong link between what was deemed transgressive religious activities and objectionable sexual practices. Moreover, sexual behaviour considered aberrant was deemed to upset political boundaries which should protect civic and national stability, especially when this behaviour was suspected of effeminacy. Such thinking appears to inform both Romans 1:18–32 and Wisdom of Solomon 14:12–14. Focussing on two passages from these documents, the links between religion, sexual behaviour and politics in the context of the 1st-century Roman Empire are investigated, tracing underlying ideological intersections, connections and divergences.